Effect of Relaxation Therapy: Slow Deep Breathing on Decreasing Blood Pressure in Patients with 1st Degree Hypertension - Ardhiansyah, Toting; Sukadiono, Sukadiono; S, Suyatno H; Anas, Muhammad (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2016)
Background: Hypertension is linearly associated with cardiovascular disease morbidity and mortality. Therefore, hypertension must be prevented and treated, and controlled adequately. Early treatment of hypertension is crucial because it can prevent complications in several organs such as the heart, kidneys, and brain. The treatment of hypertension has shifted from pharmacology to non-pharmacology because of the side effects it causes. One of the non-pharmacological management for hypertensive patients is slow deep breathing exercises. The mechanism of slow deep breathing relaxation (slow deep breathing) in the respiratory system is in the form of a state of inspiration and exhalation with a frequency of breaths of 6-10 times per minute, resulting in an increase in a cardiopulmonary stretch.Objective: To determine the effect of relaxation therapy: slow deep breathing on lowering blood pressure in patients with grade 1 hypertension.Method: Pre-experimental Design One Group Pre-Post Test Design.Results: Before being given slow deep breathing relaxation therapy, patients with grade 1 hypertension had an average (mean) systolic and diastolic blood pressure of 152.16 and 93.68 mmHg. After being given slow deep breathing relaxation therapy, patients with grade 1 hypertension have an average (mean) systolic and diastolic blood pressure of 140.42 and 92.74 mmHg.Conclusion: There is a significant effect between Relaxation Therapy: Slow Deep Breathing on Decreasing Blood Pressure in Level 1 Hypertension Patients.